Formation of Students' Character Values Through the Sharing Friday Program in State Primary Schools - Sari, Uti Kumala; Palupi, Aisyah Putri Dea (Indonesian Research Journal on Education, 2024)
Education is taken through several levels. The education levels in Indonesia include early childhood education, primary education, secondary education, and higher education. The level of education must be passed sequentially, because the nature of the level of education is interrelated with each other. The purpose of this study is to know the process of the formation of student character values and to know the inhibiting supporting factors of Friday sharing activities. The type of research used is qualitative research, where researchers describe the results of research by detailing findings in the form of data obtained during the research process. The results obtained were The process of sharing Friday activities at SDN 10 Jarai showed positive results. Facilities and a series of activities available at the school support the implementation of these activities. The formation of student character values through the Friday Sharing program at SDN 10 Jarai has been effective in shaping student character values. Students are actively and enthusiastically engaged, demonstrating a positive understanding of character values such as discipline and caring. Contributing factors include positive interactions between students, the role of teachers in guiding and setting an example, and the important role of parents and society. Meanwhile, lack of student participation and parental support are inhibiting factors.